PEMEROLEHAN BAHASA IBU PADA ANAK BERUSIA 4 TAHUN (Studi Kasus Kajian Fonologi Bahasa Madura Pada Anak Berusia 4 Tahun) - wildan; rudi (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
Language is the ability to communicate with others. In this sense, it includes all means of communication through which thoughts and feelings are expressed using symbols or signs to convey meaning—such as speech, writing, gestures, numbers, drawings, and facial expressions. Language acquisition is greatly influenced by the family environment. It appears that children at the age of two often produce sound omissions and alterations in the language they speak. The analysis shows that sound omissions are influenced by the immaturity of speech organs and articulation methods, while sound changes are related to the stages of complete language acquisition.This study aims to describe the acquisition of the mother tongue in a 4-years-old child, focusing on the phonological aspects of the Madurese language. Using a case study approach, data were collected through observation and recordings of the child’s speech in family and social settings with qualitative descriptive methods.. The findings reveal that the child has acquired most phonemes in the Madurese language, although some systematic phoneme substitutions still occur. These findings indicate a distinctive phonological development process in early language acquisition. This research contributes to the field of child language studies, particularly in the context of regional languages.